The Effect of Professional Ethics, Independence, and Audit Expertise on Auditor Performance : (Survey at the Central Sulawesi Provincial Financial and Development Supervisory Agency) - Natsir, Muhammad (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
The research objective was to examine and analyze the effect of professional ethics, independence, and audit expertise on auditor performance. Meanwhile, the long-term objectives to be achieved in this study are to establish a policy on the duties and functions of auditors, so that they can improve the performance of auditors, and comply with the principles and norms in auditing (Examination). A set of Auditor professional ethics is a professional job in running it governed by the rules that have been set and each member (auditor) obeys it. The level of auditor independence is the responsibility of the public accountant profession which is expected to indirectly reflect independence and in carrying out its work it is obscured to be impartial in preparing reports on the results of audits that will be accepted by Government Agencies, the business world, and investors. In addition, auditors are required to have audit expertise in their duties which include audit expertise which includes planning audit work programs, compiling working papers and reports on audit results. To achieve specific research objectives, researchers will conduct research at the Central Sulawesi Province Financial and Development Supervisory Agency (BPKP). The data used are primary data by giving a questionnaire to each auditor at the Financial and Development Supervisory Agency of Central Sulawesi Province, and to deepen the data the researchers will conduct interviews with BPKP leaders of Central Sulawesi Province, the data are analyzed and evaluated by multiple linear regression analysis through the Normality Test, Multicollinearity. and heteroscedasticity. The results of research can contribute to the development of science, especially in the field of auditing through analysis and testing of theoretical suitability, through variables of professional ethics, independence, and audit expertise. The results of the research can be used as a source of information and as a basis for making policies related to auditor performance.